The Complexities of Green Purchase Behavior: An Investigation into Consumer Choices - Cuandra, Fendy; Tan, Kenneth; Putra, Edy Yulianto; Lady; Susanto, Stefhani (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
This study explores key techniques to encourage green purchasing behavior in Batam's food industry, which contributes significantly to pollution and resource utilization. It examines the influence of Green Purchase Attitude (GPA), Green Self-Efficacy (GSE), Subjective Norms (SN), and Environmental Knowledge (EK) on Green Purchase Intention (GPI) and Green Purchase Behavior (GPB). The results show that GPA does not significantly affect GPB; SN does not significantly affect GPI or GPB, either directly or indirectly; and EK does not significantly affect GPB. The study addresses a gap by centering on Batam consumers and contributes a novel approach by applying the Theory of Reasoned Action as the grand theory. It also recognizes GPI as a mediating variable in understanding green purchasing behavior. This study contributes to the body of knowledge by showing that GPA, SN, and EK don't directly lead people to make green purchases. Instead, results suggest that GPI and GSE significantly affect green purchase behavior. By examining both direct and indirect effects, the study improves our understanding of how psychological factors influence green purchasing. This helps build better theories for predicting how people will act sustainably and guides future research.